2016
DOI: 10.1161/jaha.116.004399
|View full text |Cite
|
Sign up to set email alerts
|

Histological Findings and Predictors of Cerebral Debris From Transcatheter Aortic Valve Replacement: The ALSTER Experience

Abstract: BackgroundHistopathological analyses of debris captured by a cerebral protection system during transcatheter aortic valve replacement have been reported, but the origin of the captured debris was not determined and risk factors were not defined.Methods and ResultsEmbolic debris was analyzed from 322 filters used in a dual‐cerebral‐filter protection system implemented during transcatheter aortic valve replacement for 161 patients (mean age 81 years, 82 male [51%], logistic EuroSCORE 19% [interquartile range 12–… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
30
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 44 publications
(34 citation statements)
references
References 30 publications
(66 reference statements)
4
30
0
Order By: Relevance
“…In >90% of cases this thrombus material was attached to tissue and/or foreign material. The rate of acute thrombus material is in line with the data from other studies utilizing the Sentinel CPS in endovascular procedures (74%–100%) 10, 12, 14, 15. The thrombogenicity of endovascular catheters cannot be avoided completely, yet an ACT level >300 s should be achieved in every left‐sided procedure, especially in long‐lasting procedures such as VT ablation.…”
Section: Discussionsupporting
confidence: 82%
See 2 more Smart Citations
“…In >90% of cases this thrombus material was attached to tissue and/or foreign material. The rate of acute thrombus material is in line with the data from other studies utilizing the Sentinel CPS in endovascular procedures (74%–100%) 10, 12, 14, 15. The thrombogenicity of endovascular catheters cannot be avoided completely, yet an ACT level >300 s should be achieved in every left‐sided procedure, especially in long‐lasting procedures such as VT ablation.…”
Section: Discussionsupporting
confidence: 82%
“…Since calcification is 1 major reason for aortic stenosis, it is not surprising that the rate of calcified debris observed during TAVR and valve‐in‐valve procedures was reported to be much higher (46%–73%),14, 15 whereas for MitraClip and LAA closure procedures no calcified debris was found 12, 13…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…TAVR source of cerebral emboli is multiple in origin and includes friable aorta, heavily calcified aortic arch and stenotic valve. These areas strictly correspond with the manipulations during pre‐, post‐dilatation and implantation itself, in particular in case of repositioning . Over the last few years the totality of evidence concluded from several cerebral embolic protection studies with TAVR have shown consistent device safety and improvement in clinical outcomes and neuroimaging findings compared to control subjects .…”
Section: Introductionmentioning
confidence: 82%
“…A recent analysis of material captured through use of an embolic protection device during mitral valve repair showed that polymer embolism occurred as frequently as acute thromboembolism (86%), with native tissue emboli (64%) and organizing thrombi (29%) noted less often 18 . Frequent polymer coating emboli have also been affiliated with other percutaneous procedures 19,20 . Thus, polymer embolism should be included in the differential of unanticipated ischemic or inflammatory complications as well as unexplained vasculopathies occurring during the post-procedural clinical setting.…”
Section: Discussionmentioning
confidence: 99%